An improvement of mechanical properties of ductile iron and niobium alloyed ductile iron through new heat treatment cycles / Bulan Abdullah - Abdullah, Bulan (Institute of Graduate Studies, UiTM, 2012)
This research is focused on three different heat treatments and they are austempering, tempering and a new heat treatment cycle of ductile iron and niobium alloyed ductile iron. The selection of all heat treatment parameters were based on TTT and CCT diagram which were simulated by JMart Pro Software. The microstructures were observed after etching with 2% Nital using light microscopy and Scanning Electron Microscope (SEM). The structures were verified by XRD analyses.